Mitigasi Risiko Usaha Mikro dan Kecil Berbasis Maqashid Syariah: Pengabdian - Soeharjoto Soeharjoto; Deden Misbahudin Muayyad; Firdayetti; Debbie Aryani Tribudhi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Micro and Small Enterprises contribute significantly to strengthening inclusive economies and creating jobs. In reality, they still face complex business risks due to limited risk management capacity, especially those integrated with Sharia principles. This community service activity aims to enhance the literacy and risk mitigation capacity of Micro and Small Enterprises actors through an integrative and sustainable Maqasid Syariah-based approach. The participatory approach method is used by providing training and mentoring conducted at the Global Cahaya Nubuwwah Insani Foundation, Islamic Entrepreneurship Boarding School, in Neglasari Village, Darangdan District, Purwakarta Regency, West Java. Results of the activities show an improvement in the participants' ability to identify, analysis, and formulate risk mitigation strategies systematically from financial, operational, market, and Shariah aspects. Participants are also able to integrate the principles of Maqasid Syariah into business practices, particularly in ḥifẓ al-māl, ḥifẓ ad-dīn, ḥifẓ an-nafs, ḥifẓ al-‘aql, and ḥifẓ an-nasl. The main output of this activity is the formation of an adaptive and applicable risk mitigation model for Micro and Small Enterprises based on Maqasid Syariah. This activity has practical, academic, and policy implications in the development of a value-based risk management model to support the strengthening of a resilient, ethical, and competitive Sharia Micro and Small Business ecosystem in the modern economic era. The activities carried out face challenges such as time constraints, the heterogeneity of participants' education and literacy, access to digital technology, and resistance to changing business habits. Therefore, in the next program, these activities need to be conducted with a sustainable and adaptive approach.